LUDWIG WITTGEINHSTEIN'S SPIRITUAL HERITAGE: PHILOSOPHICAL FOUNDATIONS AND SOCIAL SIGNIFICANCE - Narzukulova Ferangiz (Sciental Journals Publishing, 2025)
This article analyzes the spiritual heritage of the famous philosopher Ludwig Wittgenstein from the point of view of philosophical foundations and its significance for society. The author, highlighting Wittgenstein's views on language, logic, and thought, tried to show the inextricable connection of his philosophical approaches with modern ideas. The article also analyzes Wittgenstein's thoughts as an important factor influencing the culture of communication, social consciousness, and moral views. According to him, the nature and structure of language not only shape thought processes, but also determine the relationships of people in social life. The article highlights the relevance of Wittgenstein's philosophy in the modern era and reveals its impact on education, scientific research, and cultural heritage.
Keywords: Ludwig Wittgenstein, philosophy, language and logic, analytical philosophy, spiritual heritage, social consciousness, thought, communication, ethical views, modern philosophical ideas.